Pemanfaatan Digital Payment Pada Café Cetroo Coffee Karawang - Ninik Marera; Nurul Fadillah; Santi Pertiwi Hari Sandi; Dwi Epty Hidayaty (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
The purpose of this observation is to increase the efficiency of financial transactions and financial and inventory management at Cafe Cetroo Coffee 120 Karawang by utilizing digital payment technology. In addition, another goal is to provide easy payment for customers and help cafes compete in an increasingly competitive market by adopting more advanced technology. As a cafe business, Cafe Cetroo Coffee 120 Karawang has utilized digital technology to increase efficiency and expand their customer reach. One of the ways Cafe Cetroo Coffee 120 Karawang makes use of digital payments is by accepting non-cash payments. In addition, Cafe Cetroo Coffee 120 Karawang also accepts payments using a debit card or credit card. Cafe Cetroo Coffee 120 Karawang also utilizes digital payments in their financial management. They use online accounting applications to monitor and manage their cash flow. With this application, they can track their income and expenses more easily, as well as generate financial reports quickly and accurately.. In conclusion, Cafe Cetroo Coffee 120 Karawang has made good use of digital payments to increase efficiency and expand their customer reach. By accepting cashless payments, using online accounting applications, and leveraging social media for marketing, Cafe Cetroo Coffee 120 Karawang can improve their customer experience and business efficiency.